Oxygenated hydrocarbons steam reforming over Ni/CeZrGdO2 catalyst: Kinetics and reactor modeling. (22nd December 2015) - Bakhtiari, Mehrdad; Zahid, Md. Abu; Ibrahim, Hussameldin; Khan, Ataullah; Sengupta, Protyai; Idem, Raphael
Abstract: The kinetics of the steam reforming of an equimolar mixture of oxygenated hydrocarbons (Oxy-HC) over Ni / Ce 0.5 Zr 0.33 Gd 0.166 O 2 catalyst was studied in a packed bed tubular reactor (PBTR) at atmospheric pressure, a temperature range of 550–600 °C, and a steam to feed (S/F) molar ratio range of 2–6. Intrinsic kinetic data were collected in the absence of heat and mass transport limitations, which was confirmed by performing relevant kinetic analysis. A new and unique method for estimating the kinetic rate model parameters, which uses conversion error between a 2D axisymmetric PBTR simulation and experimental results, was developed and applied in this study. A modified genetic algorithm was also developed and used as an optimization tool to minimize the model error. Three different kinetic models consisting of an empirical power law model and two mechanistic Eley–Rideal (ER) models were developed and investigated. The developed power law rate model had the form ( − r A ) = 4 × 10 4 e − ( 99026 ) / R T p A 0.6 p B 0.8 for which the reaction orders w.r.t. methanol and steam were 0.6 and 0.8, respectively, with an activation energy of 99 kJ mol −1 . An ER type mechanism that postulates the dissociative adsorption of Oxy-HCR as the rate-controlling step (RDS) was found to adequately describe the Oxy-HCR with an estimate of activation energy of 103 kJ mole −1 . A comparison between the experimental rate and the corresponding rates obtained using this model yielded an average error of 7%. Highlights: Unique integral approach for kinetic analysis in packed bed tubular reactors. New modified genetic algorithm as an optimization tool to minimize rate model errors. Mechanistic kinetic model for the steam reforming of oxygenated hydrocarbon mixture. Comprehensive simulator that concurrently solves the Navier–Stokes and energy transfer equations.